LIRO Herramienta para la conservación de mariposas y experiencias de aprendizaje en entornos educativos (2024)
Colombia stands out as one of the mega diverse countries in the world where one in every ten known species inhabits the territory. In addition, it is confirmed as the most diverse in butterfly species registered with 3,877 species, among which 218 stand out that are considered endemic (Alexander von Humboldt Institute, 2022). Culturally these insects have been associated as a symbol of femininity, transformation, life, death and resurrection of the human being; They relate them to fairies, nymphs and angels, and their presence It is established in literature, symbolism and own expressions of the region (Banco de la República de Colombia, 2022).